BIOMASS AS A RESOURCE IN PRODUCTION OF GREEN ENERGY (Baština, 2022)
Business decisions of multinational companies and local entrepreneurs aimed at making a profit, as well as irresponsible behavior of the entire society are one of the causes of environmental degradation. Irresponsible behavior leads to a high level of environmental pollution which is reflected today in many aspects of human life. Namely, the use of technologies and materials harmful to human health and the environment, but also the excessive use of natural resources leaves traces on the conditions and quality of life, of present and future generations.Increased use of resources whose existence in nature is limited, has consequences for human health and their natural environment. There is a need to strike a balance in the realization of economic goals with respect for the rules of environmental protection, through the preservation of biodiversity and the use of natural resources as energy sources in a rational and sustainable way. To this end, in addition to the energy of the sun, wind and water, biomass is becoming increasingly important in agricultural production, but also as an energy source for heat and electricity.
Keywords: biomass, renewable energy sources, sustainable development, green energy